Hieracium hypochoeroides subsp. cilentanum (Asteraceae), a new taxon from S Italy - Di Gristina, Emilio; Gottschlich, Günter; Raimondo, Francesco Maria (Phytotaxa, 2016)
A new hawkweed taxon from southern Italy, Hieracium hypochoeroides subsp. cilentanum, is described and illustrated. It is endemic to Monte Cervati (Parco Nazionale del Cilento e Vallo di Diano, S Campania). Information on its ecology and taxonomic relationships is provided.